Pengaruh Model Problem-Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik - Zetriuslita, Zetriuslita; Riyanti, Nur Faddillah (UIR Press, 2026)
This study examined the effect of Problem-Based Learning (PBL) model on mathematical problem solving ability of ninth grade students of SMP Negeri 35 Pekanbaru. This research is a quasi-experimental research with non-equivalent control group design. The population in this study were all students of class IX SMP Negeri 35 Pekanbaru which amounted to 175 students, ranging from class IX.1 to IX.5. The sample in this study was taken by purposive sampling method, so that class IX.4 which amounted to 33 students as the experimental class and class IX.5 which amounted to 33 students as the control class. Data collection techniques were carried out using test techniques with mathematical problem solving ability test instruments in the form of pre-test and post-test. Data analysis techniques used are descriptive analysis and inferential analysis. The t-test results produced a significance value of 0.000 ≤ α= 0.05, indicating that the null hypothesis H_0 was rejected and the alternative hypothesis H_1 was accepted, meaning that there was a difference between the average mathematical problem-solving ability of students in the experimental class and the average mathematical problem-solving ability of students in the control class. Therefore, it can be concluded that the PBL model has an effect on students' problem-solving abilities.